TINGKAT PEMAHAMAN DAN KESIAPAN MASYARAKAT TERHADAP KEBIJAKAN REDENOMINASI BUKAN SANERING STUDI DI WILAYAH YOGYAKARTA - Wiratna Sujarweni (Journal of Accounting and Management Innovation, 2017)
Rupiah redenomination needs the public’s understanding on the policy that will be held. The research objective aims to find and analyze the public’s understanding on redenomination and the sanering, to find the public’s understanding in Yogyakarta area on the implementation of the policy. Research population was the people who live in Yogyakarta. The research sample was using purposive sampling and incidental sampling. This research was descriptive quantitative research. The analysis device was statistic descriptive. The result shows that public’s understanding level on correct redenomination as much as 45.63%, as much as 54.38% are still confuse with redenomination term. The understanding level on sanering is as much as 47.14%,meanwhile Yogyakarta’s people who doesn’t know on sanering is as much as 52.86%. The result of descriptive processing on the readiness of redenomination policy implementation is as muchas 68 peoples (68%) are ready to implement the redenomination, meanwhile 32 peoples (32%) are not ready or disagree on implementation because they are doubt on economics turmoil, budgets cuts, and unstable inflation in making the redenomination will not succeed.Keywords: understanding, readiness, redenomination, sanering